Efficacy evaluation of probiotics combined with prebiotics in patients with clinical hypothyroidism complicated with small intestinal bacterial overgrowth during the second trimester of pregnancy - Hao, Yingqi; Xu, Yajuan; Ban, Yanjie; Li, Jingjing; Wu, Bo; Ouyang, Qian; Sun, Zongzong; Zhang, Miao; Cai, Yanjun; Wang, Mengqi; Wang, Wentao (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To explore the effect of probiotics combined with prebiotics on clinical hypothyroidism during pregnancy combined with small intestinal bacterial overgrowth. Methods (1) In total, 441 pregnant women were included in this study. A total of 231 patients with clinical hypothyroidism during the second trimester of pregnancy and 210 normal pregnant women were enrolled in the lactulose methane-hydrogen breath test. The positive rate of intestinal bacterial overgrowth (SIBO), gastrointestinal symptoms, thyroid function and inflammatory factors were compared between the two groups by chi-square test and two independent sample t-test. (2) SIBO-positive patients in the clinical hypothyroidism group during pregnancy (n=112) were treated with probiotics combined with prebiotics based on conventional levothyroxine sodium tablets treatment. The changes in the methane-hydrogen breath test, gastrointestinal symptoms, thyroid function and inflammatory factors were compared before treatment (G0) and 21 days after treatment (G21) by chi-square test and paired sample t test. Results (1) The positive rates of SIBO in pregnant women in the clinical hypothyroidism group and control group were 48.5% and 24.8%, respectively. (2) The incidence of abdominal distention and constipation in the clinical hypothyroidism group was significantly higher than that in the control group, and the risk of abdominal distention and constipation in SIBO-positive pregnant women was higher than that in SIBO-negative pregnant women. (3) The serum levels of hypersensitive C-reactive protein (hsCRP), IL-10, IL-6, TNF-α, low-density lipoprotein (LDL), total cholesterol (TC), free fatty acids (FFAs) and apolipoprotein B (ApoB) in the hypothyroidism group during pregnancy were higher than those in the control group. (4) After 21 days of probiotics combined with prebiotics, the incidence of pure methane positivity in the methane-hydrogen breath test in the G21 group was significantly reduced, and the average abundance of hydrogen and methane at each time point in the G21 group was lower than that in the G0 group. (5) The incidence of constipation in the G21 group was significantly lower than before treatment. (6) The levels of serum TSH, hsCRP, IL-6, TNF-α, TC and LDL in pregnant women after probiotics combined with prebiotics were lower than those before treatment. Conclusion Probiotics combined with prebiotics are effective in the treatment of pregnant patients with clinical hypothyroidism complicated with SIBO, providing a new idea to treat pregnant patients with clinical hypothyroidism complicated with SIBO.